2009
DOI: 10.1016/j.jcps.2009.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Memory markers: How consumers recall the duration of experiences

Abstract: In the present article, we propose a three-stage memory marker model of memory for experience. The human mind generates and encodes "memory markers" of specific episodes, stores them in memory, and after a temporal delay retrieves these markers to reconstruct the experience and make relevant judgments. Rich experiences characterized by vivid stimuli seem to pass by quickly, yet feel longer when recalled after a period of time because the number of retrieved memory markers is large. We also examine situations i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
36
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(39 citation statements)
references
References 17 publications
3
36
0
Order By: Relevance
“…So a large number of changes induce a shorter experience of time, which goes hand in hand with longer representation of time: When many things happened, the situation must have been long. Ahn et al (2009), for instance, found that participants estimated a slide show with a lot of changes as shorter than a slide show with only a few changes when they were asked immediately after the presentation. After a delay of 3 days when the time judgment can only be memory-based, however, the pattern reversed and the presentation with a lot of changes was estimated as longer.…”
Section: Discussionmentioning
confidence: 99%
“…So a large number of changes induce a shorter experience of time, which goes hand in hand with longer representation of time: When many things happened, the situation must have been long. Ahn et al (2009), for instance, found that participants estimated a slide show with a lot of changes as shorter than a slide show with only a few changes when they were asked immediately after the presentation. After a delay of 3 days when the time judgment can only be memory-based, however, the pattern reversed and the presentation with a lot of changes was estimated as longer.…”
Section: Discussionmentioning
confidence: 99%
“…From a relatively short temporal perspective, a particular situation can be perceived to pass quickly if attentional engagement in the situation is high (Block et al, 2010). On the other hand, from a longer temporal perspective, a large number of changes happening in a short period of time makes people remember that time period as long, which can be explained by a lot of changes leaving a richer memory trace, which increases the remembered duration 12 (Ahn, Liu & Soman, 2009). In sociology, lengthening and shortening of subjective temporal experience was investigated by Flaherty (1993Flaherty ( , 1999, who found that when the density of conscious 10 Music is only conceivable as consisting of extended moments, melodies, and phrases, which inter-connect individual musical elements.…”
Section: Compression Protraction and Acceleration Of Timementioning
confidence: 99%
“…XV) as the time interval, a few seconds in length, in which we experience the flow of events as being simultaneously available to perceptual or cognitive analysis. 12 The study by Ahn, Liu and Soman (2009) showed that participants in a presentation estimated a slide show with a lot of changes as shorter than a slide show with only a few slides immediately after the presentation, but after 3 days, when their time judgment was memory-based, the more dynamic presentation with a lot of changes was estimated as longer.…”
Section: Compression Protraction and Acceleration Of Timementioning
confidence: 99%
“…Specifically, an individual's cognitive system produces and stores single pieces of information from the relevant real-time experiences, much like many of us would take photographs of a vacation and keep them in a photo album (Ahn et al, 2009). These unique pieces of information are later recalled from memory and used as a proxy to estimate clock duration.…”
Section: Introductionmentioning
confidence: 99%
“…These unique pieces of information are later recalled from memory and used as a proxy to estimate clock duration. When more pieces of information are recalled from memory, longer duration estimates are produced and vice versa (Ahn et al, 2009;Areni and Grantham, 2009;Bailey and Areni, 2006;Mattel and Meck, 2000;Staddon andHiga, 2006, Ulrich et al, 2006).…”
Section: Introductionmentioning
confidence: 99%